2013
DOI: 10.7763/ijbbb.2013.v3.184
|View full text |Cite
|
Sign up to set email alerts
|

Systems Biology Study of Yeast Mitogen Activated Protein Kinase (MAPK) Cascade for Novel Drug Target Identification against Fungal Pathogens

Abstract: Abstract-Novel drug target identification and drug discovery are potential fields of systems biology which is recently being implemented against various pathogens based on differential biological processes of host and pathogen. Due to closer extent of biological similarity of eukaryotic fungal pathogens with their hosts, it has been urgent to find out novel drug targets against fungal pathogens. It is seen that mitogen activated protein kinase (MAPK) cascade transmits signals from outer cell surface to the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In the present study, macelignan had antifungal activity only against C. neoformans, other than A. apis , which might infer the inhibition of MPK1 and/or HOG pathways. Recently, a systems biology study confirmed MPK1 among 11 MAPK molecules as the best target for antifungal drugs ( 39 ). Therefore, inhibition of A. apis and C. neoformans growth by macelignan treatment can be assumed through regulation of MPK1 and/or HOG1 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, macelignan had antifungal activity only against C. neoformans, other than A. apis , which might infer the inhibition of MPK1 and/or HOG pathways. Recently, a systems biology study confirmed MPK1 among 11 MAPK molecules as the best target for antifungal drugs ( 39 ). Therefore, inhibition of A. apis and C. neoformans growth by macelignan treatment can be assumed through regulation of MPK1 and/or HOG1 pathways.…”
Section: Discussionmentioning
confidence: 99%